Screening of Yeasts for Selection of Potential Strains and Their Utilization for In Situ Microbial Detoxification (ISMD) of Sugarcane Bagasse Hemicellulosic Hydrolysate - Soares, Luma C. S. R.; Chandel, Anuj K.; Pagnocca, Fernando C. [UNESP]; Gaikwad, Swapnil C.; Rai, Mahendra; da Silva, Silvio S. (Springer Nature, 2016)
Many toxic compounds are produced and released in the hemicellulosic hydrolyzates during the acid pretreatment step, which are required for the disruption of the lignocelluloses matrix and sugars release. The conventional methods of detoxification i.e. overliming, activated charcoal, ion exchange or even membrane-based separations have the limitations in removal of these toxic inhibitors in fermentation process. Hence, it is imperative to explore biological methods to overcome the inhibitors by minimizing the filtration steps, sugar loss and chemical additions. In the present study we screened sixty-four strains of yeasts to select potential strains for detoxification of furfural, acetic acid, ferulic acid, 5-hydroxymethyl furfural (5-HMF) as carbon and energy source. Among these strains Pichia occidentalis M1, Y1′a, Y1′b and Y3′ showed a significant decrease in the toxic compounds but we selected two best yeast strains i.e. P. occidentalis Y1′a and P.occidentalis M1 for the further experiments with an aim to remove the fermentation inhibitors. The yeasts P. occidentalis Y1′a and P.occidentalis M1 were grown aerobically in sugarcane bagasse hemicellulose hydrolysate under submerged cultivation. For each yeast, a 22 full factorial design was performed considering the variables—pH (4.0 or 5.0) and agitation rate (100 or 300 rpm), and the percentage removal of HMF, furfural, acetic acid and phenols from hemicellulosic hydrolysates were responsive variables. After 96 h of biological treatment, P. occidentalis M1 and P. occidentalis Y1′a showed 42.89 and 46.04 % cumulative removal of inhibitors, respectively.
Keywords: Dilute acid hydrolysis; Inhibitors; Microbial detoxification; Sugarcane bagasse